1995
DOI: 10.1148/radiology.196.3.7644656
|View full text |Cite
|
Sign up to set email alerts
|

Graves ophthalmopathy: MR evaluation of 10-Gy versus 24-Gy irradiation combined with systemic corticosteroids.

Abstract: In treatment of GO, 24 Gy of radiation is a more effective dose than 10 Gy when combined with systemic corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 0 publications
0
11
0
5
Order By: Relevance
“…Intravenous GC pulse therapy is more effective than oral GC (response rates w80% vs w50%; (70), but an alternative regimen of 1 Gy per week over a 20-week period was equally effective and better tolerated (71). Higher doses are no more effective (72). A lower cumulative dose of 10 Gy was found to be as effective as the standard 20 Gy regimen (71).…”
Section: Box 4 Simple Measures That May Alleviate Symptoms In Gomentioning
confidence: 99%
“…Intravenous GC pulse therapy is more effective than oral GC (response rates w80% vs w50%; (70), but an alternative regimen of 1 Gy per week over a 20-week period was equally effective and better tolerated (71). Higher doses are no more effective (72). A lower cumulative dose of 10 Gy was found to be as effective as the standard 20 Gy regimen (71).…”
Section: Box 4 Simple Measures That May Alleviate Symptoms In Gomentioning
confidence: 99%
“…The most common delivered dose is 20 grays (Gy) per eye (117); this cumulative dose is usually fractionated in 10 daily doses over a 2-week period to reduce the cataractogenic effect of irradiation (116). Nakahara et al (122) reported that a cumulative dose of 24 Gy provided better results than a dose of 10 Gy. Recently, Kahaly et al (123) reported that a therapeutic scheme of 1 Gy per week over a 20-week period was equally effective and possibly better tolerated than the classical 2-week scheme.…”
Section: April 2000mentioning
confidence: 99%
“…Ravin et al (11), however, reported poor results with only lOGy retrobulbar irradiation in the treatment of GO. Nakahara et al also reported that response in the 24 Gy group was better than that in the lOGy group, in which nine out of 15 patients experienced persistent or recurrent symptoms of GO (12). A higher cumulative dose of 30…”
Section: Radiotherapy Of Graves' Ophthalmopathymentioning
confidence: 93%